The Language of Tragedy: A Lexicon-Based Sentiment Analysis of Shakespeare’s Tragic Plays - Dr S Garret Raja ImmanuelDr R Mystica, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
This paper is a lexicon-based sentiment analysis of the works of Shakespeare, where the